Diverticular Colovaginal Fistulas: What Factors Contribute to Successful Surgical Management?. Issue 9 (September 2019) - DeLeon, Michelle F.; Sapci, Ipek; Akeel, Nouf Y.; Holubar, Stefan D.; Stocchi, Luca; Hull, Tracy L.
Abstract : BACKGROUND: Diverticular disease is the leading cause of colovaginal fistulas. Surgery is challenging given the inflammatory process that makes dissection difficult. To date, studies are small and include fistula secondary to multiple etiologies. OBJECTIVE: The objectives of this study were to examine surgical outcomes of diverticular colovaginal fistulas and to identify variables associated with successful closure. DESIGN: This was a retrospective study of a prospectively maintained clinical database. SETTINGS: The study was conducted at a single tertiary referral center. PATIENTS: Women with diverticular colovaginal fistulas, who underwent surgical repair with intent to close the fistula, were included. INTERVENTIONS: Repair of colovaginal fistula through minimally invasive or open techniques was involved. MAIN OUTCOME MEASURES: Successful closure of fistula, defined as resolution of symptoms and no stoma, was measured. RESULTS: Fifty-two patients underwent surgical treatment of diverticular colovaginal fistula, 23 (44%) of whom underwent a minimally invasive approach (conversion rate of 22%). Ostomy construction and omental pedicle flaps were used in 28 (54%) and 38 patients (73%). Surgery was successful in 47 patients (90%). Accounting for secondary operations, ultimate success and failure rates were 49 (94.0%) and 3 (5.7%). There was no difference in postoperative morbidity between the 2 groups (5 patients with Clavien-Dindo III/IV complications in the success group versus 2 patients in the failure group; 10.6% vs 40.0%; p = 0.44). Failure to achieve fistula closure was not associated with perioperative variables, age, BMI, diabetes mellitus, ASA grade, steroid use, previous abdominal surgery or hysterectomy, use of omentoplasty, or ostomy. Patients who failed were more likely to be smokers (60.0% vs 12.8%; p = 0.03). LIMITATIONS: Limitations include the retrospective design and lack of power. CONCLUSIONS: Surgery is effective in achieving successful closure of diverticular colovaginal fistula. Smokers should be encouraged to stop before embarking on an elective repair. Although the use of fecal diversion and omental pedicle flaps did not correlate with success, they should be used when clinically appropriate. See Video Abstract at http://links.lww.com/DCR/A983 . FÍSTULAS COLOVAGINALES DIVERTICULARES ¿QUÉ FACTORES CONTRIBUYEN AL ÉXITO DEL TRATAMIENTO QUIRÚRGICO?: ANTECEDENTES: La enfermedad diverticular es la causa principal de fístulas colovaginales. La cirugía es un reto dado el proceso inflamatorio que dificulta la disección. Hasta la fecha, los estudios son pequeños e incluyen fístulas secundarias a múltiples etiologías. OBJETIVO: 1) Examinar los resultados quirúrgicos de las fístulas colovaginales diverticulares; 2) Identificar variables asociadas a un cierre exitoso. DISEÑO: Estudio retrospectivo de una base de datos clínicos prospectivamente mantenida. CONFIGURACIÓN: Centro de referencia superior. PACIENTES: Mujeres con fístulas colovaginales diverticulares, que se sometieron a una reparación quirúrgica con la intención de cerrar la fístula. INTERVENCIONES: Reparación de la fístula colovaginal mediante técnicas mínimamente invasivas o abiertas. MEDIDAS DE RESULTADOS PRINCIPALES: Cierre exitoso de la fístula definida como resolución de los síntomas y sin estoma. RESULTADOS: Cincuenta y dos pacientes se sometieron a tratamiento quirúrgico de la fístula colovaginal diverticular, 23 (44%) de los cuales se sometieron a un acceso mínimamente invasivo (tasa de conversión del 22%). La construcción de la ostomía y los pedículos omentales se utilizaron en 28 (54%) y 38 pacientes (73%), respectivamente. La cirugía fue exitosa en 47 pacientes (90%). Tomando en cuenta las operaciones secundarias, las tasas finales de éxito y fracaso fueron 49 (94.0%) y 3 (5.7%). No hubo diferencias en la morbilidad postoperatoria entre los dos grupos (5 pacientes con complicaciones de Clavien-Dindo III / IV en el grupo de éxito versus a 2 pacientes en el grupo de fracaso, 10.6% versus a 40.0%; p = 0.44). El fracaso para lograr el cierre de la fístula no se asoció con variables perioperatorios, edad, IMC, diabetes, grado ASA, uso de esteroides, cirugía abdominal previa o histerectomía, uso de omentoplastia u ostomía. Los pacientes que fracasaron eran más propensos a ser fumadores (60.0% versus a 12.8%; p = 0.03). LIMITACIONES: Las limitaciones incluyen el diseño retrospectivo y la falta de poder. CONCLUSIONES: La cirugía es efectiva para lograr el cierre exitoso de la fístula colovaginal diverticular. Se debe aconsejar a los fumadores a parar de fumar antes de embarcarse en una reparación electiva. Mientras el uso de desviación fecal y pedículos omentales no se correlacionó con el éxito, deberían utilizarse cuando sea clínicamente apropiado. Consulte el Video del Resumen en http://links.lww.com/DCR/A983 .